Upper respiratory tract manifestations in patients with ANCA-associated vasculitides and their association with the presence and type of ANCA - I. G. Smirnova; N. M. Bulanov; P. I. Novikov; I. A. Osipova; S. V. Moiseev (Научно-практическая ревматология)
Aim of the work – to compare the frequency of upper respiratory tract (URT) involvement in patients with ANCAassociated vasculitides (AAV), to reveal its main clinical and radiological patterns and to estimate their association with the serological profile (ANCA presence and type).Material and methods. This retrospective study evaluated 369 patients with granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA). The enrolled patients were diagnosed with AAV according to the ACR criteria, CHCC classification (2012) and EMA algorithm. Patients with URT manifestations underwent standard ENT assessment and X-ray/CT. Serum ANCA levels were measured by ELISA.Results. URT involvement was diagnosed in 280 (75.9%) patients with AAV. It was significantly more common amongthe patients with GPA (86.4%) and EGPA (85.5%) compared with the MPA group (29.2%) (p<0.001).URT manifestations mainly appeared as sinusitis (77.2% – GPA; 33.3% – MPA; 70.8% – EGPA) and rhinitis with crusting (87.8%, 72.2% and 16.9% respectively).Proteinase 3 ANCA positive patients had a significantly higher incidence of bone destructive URT lesions, including sinuses wall destruction (p<0.001) and saddle nose deformity (p=0.016), compared with myeloperoxidase-ANCA-positive patients. Similar results were obtained in the GPA group separately.Localized disease with isolated URT involvement was observed in 41.3% cases of ANCA negative GPA (p<0.001).Conclusion. The frequency and patterns of upper respiratory tract manifestations depend both on the nosologic form of AAV and type of ANCA. Localized forms of URT involvement can be observed in patients with GPA and are closely associated with absence of ANCA, which determines the need for especially high suspicion level.